Poemas de amor / Love Poems : Poems - Vilariño, Idea (Pitt poetry series., 2020)
Eight years before Sylvia Plath published Ariel, the Uruguayan poet Idea Vilariño released Poemas del Amor, a collection of confessional, passionate poetry dedicated to the novelist Juan Carlos Onetti. Both of her own merit and as part of the Uruguayan writers group the Generation of '45--which included Onetti, Mario Benedetti, Amanda Berenguer, and Ida Vitale--Vilariño is an essential South American poet, and part of a long tradition of Uruguayan women poets. Vilariño and Onetti's love affair is one of the most famous in South American literature. Poemas del Amor is an intense book, full of poems about sexuality and what it means to be a woman, and stands as a testament to both the necessity and the impossibility of love. This translation brings these highly personal poems to English speaking audiences for the first time side-by-side with the original Spanish language versions.